Powder for interior finish coating having moisture control property, coating liquid, and interior finish coating method using the same

JP2025036122APending Publication Date: 2025-03-14FUJIKAWA KENZAI IND +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024108945
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-07-05
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0012】 本発明の内装コーティング用粉末は、特定量のシラスバルーンと再乳化型水溶性樹脂とを含有すると共に全粉末が150μm以下の粒子径にて調整されているので、適用量の分散媒を加えて容易にコーティング液(スラリー)とでき、汎用の塗布ローラーや吹付け等で簡易に石膏ボード下地や壁紙のクロスの上からも容易に内装用のコーティングに用いることができる。 さらに、シラスバルーンに起因する調湿、消臭効果に加え、配合する混和成分の薬効、抗菌、抗カビ、抗ウイルス性、VOC(volatile organic compounds揮発性有機化合物)フリー等を長期間に亘って発揮させることができる。例えば潜熱蓄熱材料の粉末を加えることにより、所定の温度に保つ効果を長期間に亘って維持することができる。 また、この内装コーティング用粉末には活性がない骨材成分が、180重量部以下に配合されているが、この範囲であれば、ローラー作業性評価が優れている。なお、それ以上に骨材成分が配合されている場合には、ローラー作業性評価が著しく低下する。 そして、極薄塗りにて高い透湿性能等の特性を発揮することは、原料粉末が極めて効率よく利用され、より早期にコーティング膜を乾燥できて所望の効果を発揮することでもあり、費用対効果が著しく高いものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036122000001
    Figure 2025036122000001
  • Figure 2025036122000002
    Figure 2025036122000002
  • Figure 2025036122000003
    Figure 2025036122000003
Patent Text Reader

Abstract

To provide powder for interior finish coating which can be easily and simply coated using various coating rollers in which a roller part is rotated and can be coated, has moisture control performance equal to or higher than that of a finish coating material for interior finish coating using diatomaceous earth used in plaster work, and has such moisture control property as to extremely prolong antibacterial, antifungal and antiviral properties of an admixture component to be blended, a coating liquid, and an interior finish coating method using the same.SOLUTION: Powder for interior finish coating having moisture control property is prepared by blending 180 pts.wt. or less of an aggregate component, with respect to 100 pts.wt. of a powder component containing 3 to 7 wt.% of shirasu balloon and 11 to 18 wt.% of a re-emulsification-type water-soluble resin, in which the entire powder has a particle diameter controlled to 150 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an interior coating powder and coating liquid that can be easily applied using various types of application rollers that have a rotating roller portion for coating, that have moisture-regulating performance equal to or greater than that of interior finishing coating materials that use diatomaceous earth or the like used in plastering work, and that have moisture-regulating properties that can extremely prolong the antibacterial, antifungal, antiviral properties, etc., of the admixed ingredients that are mixed therewith, and an interior coating method that uses the same. [Background technology]

[0002] The first case of COVID-19 infection was confirmed in Japan in January 2020. Since then, the infection has spread rapidly, and in order to prevent the spread of infection, it has been necessary to restrain and halt economic activity on a massive scale, as well as to refrain from going out and work from home. As people spend more time at home, they require a more comfortable and safer living space, and this has led to do-it-yourself (DIY) activities in which people try to improve their living environment by themselves without asking professional contractors (plasterers and plastering craftsmen) for interior work. This activity is thought to be due in part to the fact that plastering materials such as trowels and coating materials can now be easily purchased at mass retailers, as well as the decline in the number of plasterers.

[0003] Lime plaster and clay walls are known as coating materials with moisture-regulating properties for plastering work, and furthermore, as in Patent Document 1, a method has been proposed for utilizing shirasu, a naturally occurring deposit, in which dried shirasu is combined with white cement or gypsum and mixed into building materials and architectural finishing coating materials. In addition, the present applicant has proposed an interior thin-applied finishing coating material containing a specific proportion of shirasu or shirasu balloons, inorganic powder, aggregate, etc., and a method for applying the same, in Patent Document 2, with the aim of providing a healthy coating material that combines crack resistance, adhesive strength, water retention, abrasion resistance, resistance to discoloration, moisture absorption and release, and negative ion generation effects.

[0004] These plastering coating materials are applied by a plasterer (a plastering craftsman) to the target surface of a floor, wall, etc. with a trowel or the like in a thickness of about 5 mm in Patent Document 1, and in an even thinner thickness of about 1 to 3 mm in Patent Document 2, thereby imparting properties (functions) to the target surface, such as moisture control, fire resistance, heat storage, and deodorizing properties, as well as measures against recent hypersensitivity to volatile organic compounds and sick house syndrome. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 3283799 [Patent Document 2] Patent No. 4304201 Publication DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0006] However, both Patent Document 1 and Patent Document 2 require trowel application, although only a thin layer of a few millimeters, and therefore have the problem that the finished painted surface varies depending on the plastering skill. In addition, with the aforementioned decrease in the number of plasterers, there was also the problem that it was difficult to even secure plasterers. Furthermore, as mentioned above, in recent years, plastering materials such as trowels and paints have become easily available on the Internet and at mass retailers, making DIY activities easy to carry out; however, a considerable amount of accumulated training, or in other words, skill, is required to be able to produce a beautiful painted surface.

[0007] Therefore, the present invention aims to provide an interior coating powder and coating liquid that can be easily and simply applied using various application rollers that have a rotating roller portion for coating, that have moisture-regulating performance equal to or greater than that of interior finishing coating materials that use diatomaceous earth or the like used in plastering work, and that have moisture-regulating properties that can extremely prolong the antibacterial, antifungal, antiviral properties, etc., of the mixed ingredients that are blended therein, and an interior coating method that uses the same. [Means for solving the problem]

[0008] The present invention has been proposed in view of the above, and relates to a moisture-regulating powder for interior coatings, characterized in that 100 parts by weight of powder components containing 3 to 7 wt% of shirasuboons and 11 to 18 wt% of re-emulsifiable water-soluble resin are blended with 180 parts by weight or less of aggregate components, and the particle size of the entire powder is adjusted to 150 μm or less. In addition, aggregate components refer to materials that do not undergo chemical reactions like those between cement and water and do not undergo changes within the coating (i.e. are inactive).

[0009] The present invention also provides an interior coating powder, wherein the aggregate component is at least one selected from the group consisting of plastering aggregate and latent heat storage material.

[0010] The present invention also proposes a coating liquid prepared by adding a dispersion medium to the above-mentioned powder for interior coating. The amount of the dispersion medium added, that is, the concentration, is not limited, and specifically, water is used exclusively, but alcohol, a dispersant, etc. may be used in combination.

[0011] Furthermore, the present invention also proposes an interior coating method comprising a first step of preparing the coating liquid, a second step of coating a coating target at a construction site with the prepared coating liquid by roller coating or the like to a thickness of 0.4 to 0.8 mm, and a third step of drying the coating film. Effect of the Invention

[0012] The interior coating powder of the present invention contains a specific amount of shirasu balloons and re-emulsifiable water-soluble resin, and the entire powder is adjusted to have a particle size of 150 μm or less. Therefore, by adding an appropriate amount of dispersion medium, it can be easily made into a coating liquid (slurry), and can be easily used for interior coating on plasterboard bases and wallpaper by simply spraying with a general-purpose application roller or other method. Furthermore, in addition to the humidity control and deodorizing effects attributable to the Shirasu balloons, the medicinal effects of the blended ingredients, antibacterial, antifungal, antiviral properties, and VOC (volatile organic compounds) free properties can be maintained for a long period of time. For example, by adding a powder of a latent heat storage material, the effect of maintaining a specified temperature can be maintained for a long period of time. This powder for interior coating contains 180 parts by weight or less of inactive aggregate, and within this range, the roller workability evaluation is excellent. If the aggregate is contained in a larger amount, the roller workability evaluation is significantly reduced. Furthermore, the ability to exhibit properties such as high moisture permeability even with an extremely thin coating means that the raw material powder is used extremely efficiently, allowing the coating film to dry more quickly and achieving the desired effects, making it extremely cost-effective.

[0013] Furthermore, when the aggregate component is one or more selected from plastering aggregate and latent heat storage material, an interior coating having the additional functions of each is obtained, for example, when a latent heat storage material is blended, an interior coating having high heat storage performance is achieved.

[0014] In addition, the coating liquid of the present invention is prepared in liquid form by adding a dispersion medium such as water to the interior coating powder, so that it can be quickly applied to coating, i.e., by roller application, spraying, etc.

[0015] Moreover, unlike ordinary plastering methods, the interior coating method of the present invention can produce a beautiful surface very easily without requiring special training by using a general-purpose application roller, etc. Furthermore, all of the first to third steps of forming this interior coating method can be easily performed, making it highly practical. Furthermore, the ability to exhibit properties such as high moisture permeability even with an extremely thin coating means that the raw material powder is used extremely efficiently, allowing the coating film to dry more quickly and achieving the desired effects, making it extremely cost-effective. BEST MODE FOR CARRYING OUT THEINVENTION

[0016] The material powders used in the powder for interior coating of the present invention are explained below. All powders are adjusted to have a particle size of 150 μm or less. As mentioned above, the applicant has proposed the invention described in Patent Document 2, but since a plasterer applies a layer with a trowel to a thickness of about 1 to 3 mm, the quality of the finished painted surface is greatly affected by the skill of the plasterer. Therefore, we investigated a coating that does not require the skilled techniques of a plasterer and found that it is possible to coat the target with a thickness of 0.4 to 0.8 mm, but it was important that even with this coating thickness, it would achieve performance equal to or better than that of Patent Document 2. Note that Patent Document 2 requires a thickness of approximately 1 to 3 mm, and it is extremely difficult to apply a coating thinner than that, and even if it were possible to coat it to a thickness of about 0.8 mm, sufficient properties could not be obtained. It was found that all of these problems could be solved by preparing an interior coating powder in which 180 parts by weight or less of an inactive aggregate component is mixed with 100 parts by weight of a powder component containing 3-7 wt% of shirasuboon and 11-18 wt% of a re-emulsifiable water-soluble resin, and the total powder is adjusted to a particle size of 150 μm or less, leading to the present invention. That is, the interior coating powder of the present invention can be coated with a coating liquid prepared using a dispersion medium such as water to a thickness of 0.4-0.8 mm by a simple means such as roller coating, has moisture-regulating performance equal to or greater than that of interior finishing coating materials using diatomaceous earth, and can extremely prolong the antibacterial, antifungal, antiviral properties, etc. of the mixed components to be mixed.

[0017] [Shirasu Balloon] Shirasu (white sand) means white sand in the southern Kyushu dialect, but geologically it refers to a layer of white volcanic ejecta (fine pumice, volcanic ash, etc.) that has accumulated in thick layers across southern Kyushu, including Kagoshima Prefecture. It is estimated that most of the shirasu was formed by the Ito pyroclastic flow that occurred during the major eruption of the Aira Caldera approximately 25,000 years ago. The volume of this pyroclastic flow was equal to the current volume of Mount Akagi (approximately 100 km3).3 ) is about twice as long as the 3 ), plus about 150 km of volcanic ash 3 The tephra (widespread Aira tephra) fell all over Japan. The Aira caldera is a depression (approximately 20km in diameter) that corresponds to the innermost part of Kagoshima Bay, north of Sakurajima. The magma that erupted at this time was called Shirasu (white sand) because it contained a lot of silicon dioxide and looked whitish. Volcanic ejecta called Shirasu is widely distributed in southern Kyushu, forming plateaus and hills. It is said that Shirasu erupted from the inner part of Kagoshima Bay and the Aira and Ata volcanoes at the mouth of the bay from the end of the Tertiary to the Quaternary Period, and consists of pumice flows (fission parts), pumice fall, and secondary deposits of these (shirasu in the narrow sense). As they are generally white sandy deposits, they have been called white sand or white sand since ancient times, but are now called Shirasu. In general, ejecta from eruptions (vitreous volcanic ash) is called "Shirasu" in the Kyushu region today. Shirasu is a completely inorganic powdery substance that is naturally baked at temperatures exceeding 1000℃. 3 Its composition is as shown in Table 1 below: 70% silica, 14% alumina, 3% calcium, 3% sodium, 2% ferric iron, 2% potassium, and others such as magnesium, titanium, and manganese. [Table 1] The above-mentioned shirasu is fired at high temperatures and foamed. When the volcanic glass in the shirasu is selected, dried, and heat-treated at high temperatures, the volcanic glass particles expand and become fine hollow foam particles (shirasu balloons). An example of the ingredients is shown in Table 2 below. [Table 2]

[0018] The Shirasu balloon is desirably blended in the powder for interior coating of the present invention at 3 to 7 wt %. If it is less than 3 wt %, the moisture-regulating function is low, and if it is more than 7 wt %, the finished surface strength is weakened.

[0019] For reference, silica fume is amorphous spherical fine particles of high-purity SiO2 and has no water absorption, so there are no problems with any composition ratio when re-emulsifiable water-soluble resin is used as a hardener. Therefore, silica fume is already used in many products and proposals.

[0020] [Re-emulsifying water-soluble resin] Re-emulsifiable water-soluble resins such as vinyl acetate (VEOVA), ethylene vinyl acetate, and acrylic resins are soluble in a dispersion medium such as water and are in powder form, so they can be mixed in advance in a dry state. In addition, in the interior paint powder of the present invention, it is preferable that the re-emulsifiable water-soluble resin is blended in an amount of 11 to 18 wt%. If it is less than 11 wt%, the abrasion resistance and adhesive strength to the substrate decrease. If it is more than 18 wt%, the moisture-regulating function decreases.

[0021] In addition, for the components other than the shirasuballoons and re-emulsifiable water-soluble resin described below, the desired ratios are shown when each is added, but depending on various manufacturing conditions, etc., it may not necessarily be necessary to include each of them, and it does not necessarily have to be within these ranges. As mentioned above, the interior coating powder of the present invention is applied to a target at a thickness of 0.4 to 0.8 mm. In order to easily apply this coating thickness using various application rollers, etc., it is necessary that 180 parts by weight or less of inactive aggregate components be mixed with 100 parts by weight of powder components containing the shirasu balloons and the re-emulsifiable water-soluble resin, and that the particle size of the entire powder be adjusted to 150 μm or less.

[0022] [Inorganic powder] As the inorganic powder, various inorganic powders having a particle size of about 100 μm or less that are also used in known plaster coating materials can be used, such as dolomite plaster, calcium carbonate powder, clay, etc. In the powder for interior coating of the present invention, this inorganic powder can be used in the range of 10 to 85 wt%, preferably 50 to 80 wt%, and may be determined taking into consideration workability, surface strength, and moisture control properties.

[0023] [Thickener] The thickener can be any of various types of thickeners used in known plastering coating materials, including one or more water-soluble thickeners selected from synthetic polymers such as methyl cellulose, carboxymethyl cellulose, and acrylic polymers, or natural polymers such as seaweed. Many of these water-soluble thickeners improve adhesion to the surface to be coated. Natural organic materials obtained from plants, etc., may also be used rather than synthetic organic materials. In the powder for interior coating of the present invention, it is preferable that the thickener is blended at 0.01 to 2 wt%. If it is less than 0.01 wt%, sufficient viscosity cannot be obtained, and the surface finishing workability according to various designs is poor, and the water retention performance is also inferior. If it is more than 2 wt%, the workability, finishing accuracy, and even drying after application are deteriorated.

[0024] [Pigments] As the pigment, various pigments such as titanium oxide, which are also used in known plastering coating materials, can be used. In addition, the design can be improved by adding various colors.

[0025] 〔others〕 It is also possible to use a workability improver to improve workability, or natural calcium borate (colemanite) to impart anti-mold properties. It is also possible to mix and use a VOC adsorbent to adsorb and fix VOCs. Furthermore, the water-soluble resin other than the re-emulsifiable type used as the curing agent may be used as a water retention agent or an adhesion aid. The water-soluble resins used as the water-retaining agents or adhesive assistants include synthetic polymers such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol, and acrylic; natural polymers such as starches and seaweed; clay minerals; and pulp.

[0026] The "aggregate component" used in this invention refers to a material that does not undergo a chemical reaction like cement and water, and does not undergo any change (i.e., is inactive) in concrete, and specifically refers to one or more materials selected from plastering aggregates and latent heat storage materials. These aggregates are known to have a variety of particle sizes, but the powder for interior coating of the present invention ("aggregate component" + "powder component") uses aggregates with a particle size of 150 μm or less.

[0027] [Aggregate for plastering] The plastering aggregate used in the present invention is one having a particle size of about 150 μm or less, such as zeolite or calcium carbonate. In the present invention, the plastering aggregate used as the "aggregate component" has a particle size of 50 to 150 μm, but aggregate with a particle size of 50 μm or less may be added as the "powder component" in the present invention. As for the plastering aggregate, general plastering materials are used which have a large particle size of 500 μm or more, reaching several millimeters, making them suitable for trowel application. However, these plastering materials are not applicable, and the plastering aggregate used in the interior coating powder of the present invention is one with a particle size of 150 μm or less so that the coating thickness will be 0.4 to 0.8 mm. In the powder for interior coating of the present invention, the plastering aggregate can be mixed in an amount of 180 parts by weight or less per 100 parts by weight of the powder component. By adding the aggregate component, it is possible to impart the odor absorbing function and humidity control performance that the aggregate component possesses.

[0028] [Latent heat storage material (PCM)] The interior coating powder of the present invention may contain a latent heat storage material containing a latent heat storage substance. This latent heat storage substance absorbs heat and melts when the temperature rises, and releases heat and solidifies when the temperature drops, making it suitable for maintaining a predetermined temperature for a certain period of time. Examples of the latent heat storage material include paraffin compounds, fatty acids, fatty acid esters, aliphatic ethers, aliphatic ketones, aliphatic alcohols, olefin polymers, inorganic hydrates, etc. The latent heat storage material may be used alone or in combination of two or more kinds. In particular, a combination of at least one selected from the group consisting of paraffin compounds; or the group consisting of fatty acid esters, aliphatic ketones, aliphatic alcohols, and aliphatic ethers, and a fatty acid or a fatty acid metal salt is preferred. One of these latent heat storage materials may be used alone, or two or more may be used in combination. From the viewpoint of increasing the amount of latent heat at a specific temperature, it is preferred to use one of these materials alone or two or more may be used in combination, and from the viewpoint of expanding the temperature range in which the latent heat storage material can be used, two or more may be used in combination, or three or more may be used in combination.

[0029] The latent heat amount of the latent heat storage material (latent heat of fusion and latent heat of solidification) is not particularly limited, but is preferably 100 J / g or more. If it is less than 100 J / g, the amount added to the wall material will be too large, and the properties required for the wall material (various functions such as workability, strength, and moisture control) may decrease. The latent heat storage material used as the "aggregate component" in the present invention has a particle size of 50 to 150 μm, but as described above, a particle size of 50 μm or less may be added as the "powder component" in the present invention.

[0030] The latent heat storage material used in this embodiment is preferably a solid material in which the latent heat storage substance does not liquefy even after a phase change (melting) and maintains its shape. Specifically, the latent heat storage substance is encapsulated in a microcapsule, an inorganic porous body is impregnated with the latent heat storage substance, a thermoplastic resin and a latent heat storage substance are melted and mixed, an olefin polymer, a crosslinked product of an olefin polymer, and the like. Among these, the latent heat storage substance is preferably encapsulated in a microcapsule in terms of the amount of latent heat (heat storage performance) and the material strength (heat storage substance leakage property). In the present invention, the "microcapsule" refers to a minute container for sealing the latent heat storage substance. By encapsulating the latent heat storage substance in a microcapsule, even if the heat storage substance absorbs heat and melts, it is possible to prevent the latent heat storage substance from leaking into the building wall material, and also to protect the latent heat storage substance from the external environment.

[0031] The volume average particle diameter of the microcapsules encapsulating the latent heat storage material is preferably 1 to 150 μm. If the volume average particle diameter of the microcapsules exceeds 150 μm, the design properties after application may be deteriorated, and if it is less than 1 μm, the workability during application (scattering due to fine powder, thickening of wall material, etc.) may be deteriorated.

[0032] [Coating Method] The powder for interior coating of the present invention contains each of the above-mentioned materials in the specific composition ranges described above, and can be made into a coating liquid (paint) using a re-emulsifiable water-soluble resin as a curing agent, and can be coated using a general-purpose application roller, spraying, etc. Although a general-purpose application roller has been described, it is advisable to use a microfiber roller or foam-free roller to adjust the bristles length and consider the desired finish.

[0033] As mentioned above, coating materials for plastering can be applied with a trowel or the like to a thickness of about 5 mm (for example, as described in Patent Document 1), and even the prior invention by the present applicant, which aims for a thin application, can be applied to a thickness of about 1 to 3 mm (as described in Patent Document 2). In contrast, in the present invention, it has been found that equivalent or superior properties can be achieved even with a coating thickness of 0.4 to 0.8 mm, which is only a fraction of that thickness. The fact that a very thin coating of 0.4 to 0.8 mm can exhibit properties such as high moisture permeability means that the raw material powder is used extremely efficiently, the coating film can be dried more quickly, and the desired effects are achieved, making it highly cost-effective.

[0034] The powder for interior coating of the present invention contains, as described above, powder components with a particle size of 100 μm or less, which contain 3 to 7 wt% shirasu balloons, 11 to 18 wt% re-emulsifiable water-soluble resin, 10 to 85 wt% inorganic powder, and 0.01 to 2 wt% thickener, and also contains plastering aggregate and latent heat storage material as inactive aggregate components, and the powder for interior coating of the present invention can be produced by mixing and stirring these dry components.

[0035] The interior coating method of the present invention using the interior coating powder comprises a first step of preparing the coating liquid by adding a dispersion medium such as water to the interior coating powder, a second step of coating the coating liquid to a thickness of 0.4 to 0.8 mm on a coating target at a construction site, and a third step of drying the coating film. In the first step, a suitable amount of a dispersion medium such as water is added to the interior coating powder and stirred appropriately to form a coating liquid, which is a dispersion liquid (slurry) rather than a solution. The amount of the dispersion medium such as water to be added is not particularly limited, but is added so as to form a slurry that does not cause sagging and does not interfere with the coating work. Furthermore, the stirring method is not particularly limited. The thickness in the second step is the thickness of the coating film, so the thickness in the wet state (before drying) may be slightly thicker than the specified value, and the coating method is as described above. The method for drying the coating film in the third step is not particularly limited, and may be forced drying using, for example, a handheld dryer, but in many cases, the coating film is left at room temperature. As described above, the interior coating method of the present invention has high practical value since all of the first to third steps can be carried out easily.

[0036] The interior coating solutions of Examples A, B, and C were prepared with the composition ratios shown in Table 3, and the coatings with thicknesses of 0.4 to 0.8 mm were tested and evaluated as follows for workability, surface strength, moisture-regulating performance, antibacterial properties, antifungal properties, non-flammability, and latent heat. For comparison, finishing coating materials A and B with similar component compositions were prepared and applied with a trowel or the like to a thickness of about 5 mm, and similarly tested and evaluated. [Table 3]

[0037] [Workability] [Table 4]

[0038] [Surface strength] Complies with JIS A 6909 abrasion resistance test for architectural finishing coating materials. [Table 5]

[0039] [Adhesive strength] Complies with JIS A 6909 adhesion strength test for architectural finishing coating materials. [Table 6]

[0040] [Humidity control performance] Complies with JIS A 6909 moisture absorption and release test for architectural finishing coating materials. [Table 7] 〔antibacterial〕 Complies with JIS Z 2801:2000 antibacterial performance testing method.

[0041] [Table 8]

[0042] [Anti-fungal] Compliant with JIS Z 2801:2000 antibacterial performance testing method. [Table 9] Evaluation criteria [Table 10]

[0043] [Nonflammable] [Table 11]

[0044] [Latent heat amount] Complies with JIS A 1489:2022 Measurement method for heat storage characteristics of building materials using latent heat storage materials. [Table 12]

[0045] 〔summary〕 From the above test (Example I), it was confirmed that the interior coating liquids of Examples A to C of the present invention have almost the same performance in terms of workability, surface strength, adhesion strength, moisture conditioning performance, antibacterial properties, antifungal properties, and non-flammability properties as the finishing coating materials of Comparative Examples A and B, which are several times the amount of the liquids. In addition, it was confirmed that Example C, which contains latent heat storage powder, also has excellent performance in terms of latent heat amount. Example 1

[0046] The interior coating liquid of Example A shown in Table 3 was applied (Example I). After puttying the gypsum board base of the Japanese-style room (15 m2) of a wooden house, the interior coating liquid was applied with a microfiber roller at 230 to 250 kg / m2 in the first application, and after the painted surface dried, 310 to 330 kg / m2 was applied in the second application, so that the total application amount was about 560 kg / m2. The coating thickness was 0.4 to 0.6 mm. After application of the interior coating liquid, no particular abnormalities were observed, and even after 10 months, no evidence of cracking, lifting, peeling, etc. was observed.

[0047] The interior coating liquid of Example B shown in Table 3 was applied (Example I). After sealing the vinyl wallpaper base of the entrance, hallway, and staircase of the first floor of a wooden house (first floor total: 100 m2) and the living room, kitchen, staircase, hallway, and toilet of the second floor (second floor total: 60 m2), the interior coating liquid was applied using a microfiber roller at 230 to 250 kg / m2 the first time, and after the painted surface dried, 310 to 330 kg / m2 was applied the second time, so that the total amount applied was about 560 kg / m2. The coating thickness was 0.4 to 0.6 mm. After application of the interior coating liquid, no particular abnormalities were observed, and even after 1 year and 5 months, no evidence of cracking, lifting, peeling, etc. was found.

[0048] The interior coating liquid of Example C shown in Table 3 was applied (Example I). After putty treatment of the gypsum board base of the living room (20 m2) of a wooden house, the interior coating liquid was applied once at 230 to 250 kg / m using a microfiber roller. 2 Apply 310~330kg / m2 for the second time after the surface has dried. 2 Coating, total coating weight 560kg / m 2 The coating thickness was 0.4 to 0.6 mm. After application of the interior coating liquid, no particular abnormalities were observed, and even after 10 months, no evidence of cracking, lifting, peeling, etc. was observed.

[0049] [Consideration] From the above Example I, it was confirmed that the interior coating method in which the interior coating liquid of the present invention is applied to a thickness of 0.4 to 0.6 mm sufficiently maintains the effects of humidity control performance, adhesion strength, etc. even after 10 months to 1 year and 5 months. [Example II]

[0050] [Table 13]

[0051] Using the interior coating powders of Examples 1 to 7 and Comparative Examples 1 to 4 shown in Table 13, application tests (Example II) were carried out. In this Example II, a latent heat storage material with a particle size of 150 μm was mixed as an aggregate component, and a coating liquid prepared using water as a dispersion medium was applied twice with a microfiber roller at 0.4 to 0.5 kg / m2 per application. The coating thickness was 0.6 to 0.8 mm. In addition, the latent heat storage material used is light with a bulk density of 0.6, so compared to inorganic powders such as calcium carbonate and silica sand, it takes up a larger volume in the coating liquid even with the same weight added, so it has been converted to 1. Example: When 60 parts by weight of latent heat storage material with a bulk density of 0.6 is added, it is converted to 60 / 0.6=100. In addition, thickeners such as MC, acrylic polymers, synthetic polymers, and guar gum are used as viscosity and water retention agents. Water retention agents are used when you want to retain moisture without adding too much viscosity. Clay mineral-based, pulp fiber-based, starch-based, absorbent polymer-based, etc. are used.

[0052] [Results and Discussion] As is clear from Table 13, when the latent heat storage material used as the aggregate component was 180 parts by weight or less per 100 parts by weight of the powder component, as shown in Examples 1 to 7, the roller workability was very good and the paint (coating liquid) properties were very excellent. In particular, in Examples 4 to 6, the composition of the powder component having a particle size of less than 50 μm was changed, and although the hiding power of the base, finish, and surface strength were somewhat inferior to Examples 1 to 3 and 7, they are good examples. In contrast, in Comparative Examples 1 to 4 in which the aggregate component (latent heat storage material) was added in an amount greater than 180 parts by weight, the amount of aggregate component was too high, making it difficult to combine into a paint. In particular, in Comparative Example 1, although the other components were the same as in Example 1, the aggregate component was too high, making it difficult to combine into a coating liquid. Comparative Example 2 is an extreme example in which a coating liquid does not become uniformly liquid if there are only aggregate components with large particle diameters and no powder components with fine particle diameters. Comparative Example 3 is an example in which a large amount of aggregate components was added relative to the mix of Example 6, and therefore the hiding power of the base was good, but the other finishes and surface strength were poor.

Claims

1. This moisture-regulating powder for interior coating is characterized in that 100 parts by weight of powder components containing 3-7 wt % of shirasuboon and 11-18 wt % of re-emulsifiable water-soluble resin are mixed with 180 parts by weight or less of aggregate components, and the particle size of all the powders is adjusted to 150 μm or less.

2. 2. The interior coating powder according to claim 1, wherein the aggregate component is at least one selected from the group consisting of inorganic powder, plastering aggregate, and latent heat storage material.

3. A coating liquid prepared by adding a dispersion medium to the powder for interior coating according to claim 1 or 2.

4. A method for interior coating comprising: a first step of preparing the coating liquid according to claim 3; a second step of coating a coating target at a construction site with the prepared coating liquid to a thickness of 0.4 to 0.8 mm; and a third step of drying the coating film.

Citation Information

Patent Citations

  • Groundwork modifier and its modification

    JP2001040277A

  • Paint material for interior thin-painting finish having humidity adjustment performance, manufacturing method therefor, wall material for interior thin-painting finish having humidity adjustment performance, and executing method therefor

    JP2008101436A

  • Raw materials for plastering wall finishes, plastering wall finishes, and methods for manufacturing these materials.

    JP3283799B2

  • A moisture-regulating thin-layer interior finishing coating material, a method for manufacturing the same, a moisture-regulating thin-layer interior wall finishing material, and a method for applying the same.

    JP4304201B2